The Effect of Some Control Material on the Density of the Root-Knot Nematode (Meloidogyne incognita) in Laboratory and Field (Damascus University Journal of agriculture sciences, 2021)
The study included two types of experiments (in pots was carried out in the laboratories of the Biological Control Research and Studies Center at the Faculty of Agriculture, University of Damascus and field experiments in the Syrian coast in 2018). The aim of the study was to evaluate the efficiency  of organic fertilizer and some new synthetic pesticides used by farmers in controlling the root-knot nematode (Meloidogyne incognita) on tomato(Markoni f1). Results of pots experiments showed that tested treatments have significant differences in density of Juveniles of the M. incognita, the treatment of Velum prime has the highest  effect in controlling (M. incognita) which eliminated it completely, followed by the treatment of Novo safe with the density of (1.00 Juvenile /50 cm3 soil), then the treatment of Neem cake with the density of (2.00 Juvenile /50 cm3 soil) compared to the infested control which was (3.33 Juvenile /50 cm3 soil). Some of tested treatments also showed a significant increasing in growth indicators: plant height and weight of plants compared to  the infested control. The Velum prime treatment gave superiority in plant height and root weight which were (58.30cm - 5.58g) compared to the rest of the treatments. Field results showed that the Velum prime 1.5 treatment was superior in controlling the root-knot nematode which density decreased significantly (2.7 Juvenile /50 cm3 soil), followed by Velum prime 1.25 treatment (15.7 Juvenile /50 cm3 soil). The results also showed that the number of root nodes varied according to the treatment, where no nodes were observed in the Velum prime 1.5 pesticide treatment, the Galling Index was also zero, and the Velum prime 1.5 pesticide achieved the highest wet root weight which reached 25.50g.
Keywords: Nematode; Meloidogyne incognita; Neem cake; Velum prime